Introduction - Rodrigo Basco; Roger Stough; Lech Suwala (Family Business and Regional Development, 2021)
Family business participation in economic activities has been a common phenomenon since pre-industrial societies, and its importance has evolved throughout time and across spatial contexts. These factors have often been neglected in family business and regional studies. Taking this research gap into account, this edited collection aims to deepen our understanding of the role family frms play in regional economies. Another objective is to recognise the effect of regional contexts on family frms by encouraging the cross-fertilisation of ideas, theories, and research methods between the two felds. In particular, our collection explores the relationship between families, frms, and regions and the extent to which these connections contribute to regional economic and social development. We therefore invite readers on this collective journey as we explore two seldom studied questions: (1) What role do family frms play in regional development? (2) How do different spatial regional contexts shape family firms' operations and performance?
Keywords: D10; R2; O18; R11; R12; R50; 330; Family Firms; Regional Development; Regional Economics; Economic Geography